2016
DOI: 10.1016/j.clinimag.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists' interpretive skills in screening vs. diagnostic mammography: are they related?

Abstract: Purpose To determine whether radiologists who perform well in screening also perform well in interpreting diagnostic mammography. Materials & Methods We evaluated the accuracy of 468 radiologists interpreting 2,234,947 screening and 196,164 diagnostic mammograms. Adjusting for site, radiologist, and patient characteristics, we identified radiologists with performance in the highest tertile and compared to those with lower performance. Results A moderate correlation was noted for radiologists’ accuracy when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As Gunderman notes, expertise in one radiologic domain does not necessarily apply to every domain (Gunderman et al, 2001). For instance, Beam et al (2006) and Elmore et al (2016) note that mammographers have two distinct tasks: (1) Interpretation of screening mammograms and (2) Interpretation of abnormal screening mammographic findings. The first task requires evaluation of standard images from a large population of individuals without specific signs or symptoms (considered ‘perceptual’), whereas the second task requires careful analysis of specific abnormalities (considered more ‘cognitive’) (Beam et al, 2006; Elmore et al, 2016).…”
Section: Challenges To the Functional Definition Of Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…As Gunderman notes, expertise in one radiologic domain does not necessarily apply to every domain (Gunderman et al, 2001). For instance, Beam et al (2006) and Elmore et al (2016) note that mammographers have two distinct tasks: (1) Interpretation of screening mammograms and (2) Interpretation of abnormal screening mammographic findings. The first task requires evaluation of standard images from a large population of individuals without specific signs or symptoms (considered ‘perceptual’), whereas the second task requires careful analysis of specific abnormalities (considered more ‘cognitive’) (Beam et al, 2006; Elmore et al, 2016).…”
Section: Challenges To the Functional Definition Of Expertisementioning
confidence: 99%
“…Both studies found only a moderate correlation between radiologists’ performance in the two domains. In other words, proficiency in one area did not guarantee proficiency in the other (Beam et al, 2006; Elmore et al, 2016). The presence of wide disparities in screening and diagnostic interpretive skills in the same individual has been described as ‘expertise disequilibrium’ (Beam et al, 2006).…”
Section: Challenges To the Functional Definition Of Expertisementioning
confidence: 99%
“…Reports on variability in interpretation of screening (1719) and diagnostic (20,21) mammography investigated the impact of physician characteristics such as subspecialty training, years of experience, and volumes of yearly interpreted examinations on improved performance (2224). In our analysis of facility characteristics, community practices were more likely to utilize subdivisions in their category 4 examinations ( P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of radiologists, previous knowledge and expertise (including their a priori expectations about a task) can change the features they may use to accomplish their task goals. Further, the interpretation of medical imaging is highly task-dependent: radiologic expertise in one domain does not necessarily rely on the same skills as expertise in another domain ( Beam, Conant, & Sickles, 2006 ; Elmore et al, 2016 ; Gunderman et al, 2001 ). Task demands can similarly change within a specific domain and therefore affect search behavior: for example, in patients with known renal cell cancer, radiologists may prolong their search of the lungs, looking carefully for nodules that might represent metastatic lesions.…”
Section: Introductionmentioning
confidence: 99%